2000
DOI: 10.1111/j.1530-0277.2000.tb02066.x
|View full text |Cite
|
Sign up to set email alerts
|

Heart Mitochondrial Respiratory Chain Complexes Are Functionally Unaffected in Heavy Ethanol Drinkers Without Cardiomyopathy

Abstract: Chronic ethanol drinkers without cardiomyopathy exhibit normal MRC activity in the heart and do not show increased oxidative damage in myocardial membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Similarly, using autopsy samples obtained from patients with the clinical diagnosis of ACM, Vikhert et al (35) found atrophy of myofibrils, dilation of the sarcoplasmic reticulum, increased number of mitochondria as well as mitochondriosis (small mitochondria closely packed together), and an increase in the number of lysosome-like structures. In contrast to the aforementioned studies, Mirό et al (56) did not find evidence of mitochondrial injury in biopsy samples obtained from long-term ethanol drinkers ( n = 10). Specifically, no changes in indices of mitochondrial respiratory chain complexes (i.e., complex I, II, III, and IV activity) or evidence of lipid peroxidation were found.…”
Section: Mitochondrial Bioenergetics/stressmentioning
confidence: 78%
See 1 more Smart Citation
“…Similarly, using autopsy samples obtained from patients with the clinical diagnosis of ACM, Vikhert et al (35) found atrophy of myofibrils, dilation of the sarcoplasmic reticulum, increased number of mitochondria as well as mitochondriosis (small mitochondria closely packed together), and an increase in the number of lysosome-like structures. In contrast to the aforementioned studies, Mirό et al (56) did not find evidence of mitochondrial injury in biopsy samples obtained from long-term ethanol drinkers ( n = 10). Specifically, no changes in indices of mitochondrial respiratory chain complexes (i.e., complex I, II, III, and IV activity) or evidence of lipid peroxidation were found.…”
Section: Mitochondrial Bioenergetics/stressmentioning
confidence: 78%
“…Differences among human studies may relate to a number of reasons, such as duration of drinking, degree of myocardial dysfunction, and experimental techniques. Interestingly, in the more contemporary study by Mirό et al, ethanol drinkers had been receiving pharmacologic treatments such as beta-blockers, which (depending on the type) have anti-oxidant effects (56). …”
Section: Mitochondrial Bioenergetics/stressmentioning
confidence: 99%